Conversations with the turtles: on the ideological conundrums of our times - Espino, Nilson Ariel (Cambridge University Press, 2024)
Polarization often results from deficient forms of social belonging, caused primarily by stark social inequalities. These inequalities then generate psychological responses that both create and worsen polarization. Yet social stability is possible. In this provocative and original book, Nilson Ariel Espino argues that our current ideological polarizations can be best analysed as springing from the contradictions of modernity and its obsessions. Using culture as a founding and organizing dimension, the author disassembles the typical dichotomies of left versus right, or conservatism versus progressivism, and reveals the opposing sides as mutually interdependent positions that struggle with cultural paradoxes they are ill-suited to address. Written with clarity and verve for the general reader, this book brings classic concepts of cultural anthropology to bear on the key preoccupations of today's world, from poverty and inequality, to political instability and the environmental crisis.